A Massive Yellow Supergiant in the Far Outer Disk of M31: Evidence for in Situ Massive Star Formation beyond the Optical Radius - Pinjian Chen; Bingqiu Chen; Haibo Yuan; Xuan Fang; Xiaodian Chen; Chao-Wei Tsai; Kai Zhang; Xiaowei Liu (The Astronomical Journal)
While massive stars are known to shape galactic ecosystems, their formation has long been assumed to require the high-density environments of inner galactic disks. This paradigm is challenged by mounting evidence of young massive stars in extended galaxy outskirts, yet direct confirmation of in situ massive star formation in such extreme low-density environments remains scarce. Here, we present the discovery of LAMOST J0048+4154, a massive yellow supergiant situated at a deprojected galactocentric distance of ∼34 kpc in M31, making it the most distant massive star confirmed in this galaxy. Through spectroscopic and photometric analyses, we classify J0048+4154 as an F5–F8I supergiant with an effective temperature of $635{7}_{-118}^{+121}$ K and a luminosity of ${log}\,L/L_{\odot }=5.0{0}_{-0.06}^{+0.06}$ , corresponding to an ∼18 M _⊙ progenitor and an age of ∼10 Myr. FAST H i observations reveal close spatial and kinematic alignment between the star and a faint H i external arm, suggesting in situ formation in a region of low gas density. The presence of other UV-bright, early-type stars in the vicinity further supports low-level recent star formation in M31’s very outer disk. These findings challenge the prevailing assumption that massive star formation is confined to inner disks or classical star-forming regions and underscore the need to reexamine the role of spiral galaxy outskirts in fueling and sustaining star formation. J0048+4154 thereby expands our understanding of the extent of M31’s young stellar component and exemplifies how outer disks may harbor conditions conducive to forming massive stars despite low-density environments.